PEMETAAN NERACA SUMBERDAYA AIR KABUPATEN SABU RAIJUA, NUSA TENGGARA TIMUR, INDONESIA - Roswidyatmoko Dwihatmojo; Dwi Maryanto (Department of Urban and Regional Planning, Diponegoro University, 2015)
The balance of water resources reflects changing water resource potential within a certain time. Sabu Raijua Regency is a regency in East Nusa Tenggara Province that has physical problems in the water supply. This study aims to identify the potential, utilization, and the balance of water resources in Sabu Raijua Regency. The method used is quantitative and spatial analysis to calculate the potential, utilization, and balance water resources. The results showed potential and utilization of water in Sabu Raijua. The balance of water resources showed greater ‘aktiva’ than ‘pasiva’, and there is still a balance of 415,453,645.75 m3/year. This condition also shows that Sabu Raijua Regency has a surplus of water resources within a period of one year. However, in a certain period (July-September) it experiences a deficit of water resources so that it needs good water resource management to anticipate the problem. © 2015 GJGP UNDIP. All rights reserved.